Microbiome Modulation in Pediatric Leukemia: Impact on Graft-Versus-Host Disease and Treatment Outcomes: A Narrative Review - Samuel Bogdan Todor; Cristian Ichim (Children)
The gut microbiome significantly influences the outcomes of pediatric leukemia, particularly in patients undergoing hematopoietic stem cell transplantation (HSCT). Dysbiosis, caused by chemotherapy, antibiotics, and immune system changes, contributes to complications such as graft-versus-host disease (GVHD), gastrointestinal issues, and infections. Various microbiome-related interventions, including prebiotics, probiotics, postbiotics, and fecal microbiota transplantation (FMT), have shown potential in mitigating these complications. Specific microbial signatures have been linked to GVHD risk, and interventions like inulin, Lactobacillus, and SCFAs (short-chain fatty acids), particularly butyrate, may help modulate the immune system and improve outcomes. FMT, while showing promising results in restoring microbial balance and alleviating GVHD, still requires careful monitoring due to potential risks in immunocompromised patients. Despite positive findings, more research is needed to optimize microbiome-based therapies and ensure their safety and efficacy in pediatric leukemia care.